INFLUENCE OF ORGANIZATIONAL CLIMATE AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE WITH LEADERSHIP AS A MODERATING VARIABLE - Febryantahanuji, Febryantahanuji; Hannief Giarni (Pusat Riset dan Inovasi Nasional, 2022)
The aim from this research analyzes work ethic and job satisfaction influence towards official job performance with leadership as moderating variable. Population that canvassed entire official at Biro Umum Sekretariat Daerah Provinsi Jawa Tengah with total as much as 342 person. In this research total sample taken 103 person with Slovin formula. Analyzer that used in this research moderated regression analysis Hypothesis testing 1 known that value t count = 2.832 > t table = 1.658 with number significance = 0.009 < α = 0.05 (significant). Thereby so hypothesis (H1) that work ethic excelsior so also official job performance proved. Hypothesis testing 2 be known that value t count = 2.854 > t table = 1.658 with number significance = 0.005 < α = 0.05 (significant). Thereby so hypothesis (H2) that job satisfaction excelsior so also official job performance proved. Hypothesis testing 3 known that value t count 2.527 > t table = 1.658 with number significance = 0.017 < α = 0.05 (significant). Thereby so hypothesis (H3) that existence better leadership will brace influence work ethic towards official job performance proved. Hypothesis testing 4 known that value t count 2,784 > t table = 1.658 with number significance = 0.012 < α = 0.05 (significant). Thereby so hypothesis (H4) that existence better leadership will brace influence job satisfaction towards official job performance proved.